2001
DOI: 10.1046/j.1440-1622.2001.02150.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of the anatomy of the venous drainage of the intrahepatic and extrahepatic bile ducts and its relevance to the practice of hepatobiliary surgery

Abstract: The satisfactory results of end-to-end anastomosis in whole liver transplantation depends partly on the presence of adequate venous drainage. This has been amply demonstrated by the injection studies. This would indicate that the poor results of end-to-end repair of the bile duct after surgical trauma results from other factors such as poor technique, devascularization of the cut ends due to trauma, and carrying out the anastomosis under tension. After resection of the hilum for cholangiocarcinoma the venous d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 9 publications
0
27
0
5
Order By: Relevance
“…22 This system runs along the CBD and HA in the arteriobiliary portion of the portal pedicle anterior to the portal vein and is composed of at least one big vessel along the CBD or hepatic artery or both. This system is comparable to the marginal veins described by Vellar 23 and begins from PSPDV and pyloric veins and divides to form a venous network in the hilar plate. This hilar venous network sends branches to the veins of segments adjacent to the hilum like caudate and quadrate lobes.…”
Section: Venous Drainage Of Biliary Tractmentioning
confidence: 64%
See 2 more Smart Citations
“…22 This system runs along the CBD and HA in the arteriobiliary portion of the portal pedicle anterior to the portal vein and is composed of at least one big vessel along the CBD or hepatic artery or both. This system is comparable to the marginal veins described by Vellar 23 and begins from PSPDV and pyloric veins and divides to form a venous network in the hilar plate. This hilar venous network sends branches to the veins of segments adjacent to the hilum like caudate and quadrate lobes.…”
Section: Venous Drainage Of Biliary Tractmentioning
confidence: 64%
“…26 The paracholedochal venous plexus the right gastric vein. 23 In postmortem specimens Vellar 23 has demonstrated retrograde filling of the marginal veins and the venous plexus on the CBD after transecting the CBD and all communicating veins at the upper border of duodenum and suggested that this bidirectional pathway ensures good results seen in end-to-end anastomosis in liver transplantation.…”
Section: Venous Drainage Of Biliary Tractmentioning
confidence: 98%
See 1 more Smart Citation
“…The paracholedochal plexus comprises of two veins, the 3 o'clock and 9 o'clock marginal veins, that run parallel to the CBD in the hepatoduodenal ligament, but not in contact with the CBD wall (Figure 1), and are interconnected with multiple large transverse channels. [8][9][10][11] Near the hilum, these marginal veins can enter the hepatic substance, join the right and left branches of portal vein or join the hilar venous plexus. Just below the hilum, the marginal veins are connected to the patent part of portal vein and its tributary, the right gastric vein.…”
mentioning
confidence: 99%
“…The hilar venous plexus can drain into marginal veins of PCD venous plexus, communicate with the veins of caudate lobe and segment IV or drain into sinusoids ( Figure 2). 8,9 The hilar plexus can also directly drain into nearby branches of portal vein via peribiliary venules (Figure 2). 12 Scanning electron microscopy of corrosion casts of the microvascular arrangement of CBD wall in animals and humans has provided evidence for the presence of two more intrinsic vascular plexuses: the subepithelial and intramural venous plexuses which are connected to the ECD and PCD venous plexuses (Figure 3).…”
mentioning
confidence: 99%